Online social functioning of students of Polish higher education institutions - Walter, Natalia (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The paper was devoted to the issue of social functioning of Polish higher education institution students online. The internet is a social space, which offers opportunities for civic engagement, and online political activism; it can also be a place of interactions, such as social support, which lead to the improvement of individual mental well-being. The paper outlines some of the results of a study carried out as part of a State Agency for the Prevention of Alcohol-Related Problems project (40/3.4.3/19/DEA) in 2019 on a group of 4503 women and men, studying at Polish higher education institutions. The tool used to study the support was the Multidimensional Perceived Social Support Scale, complemented by statements concerning online support. In order to investigate the phenomenon of social and civic engagement, the study used a scale of 14 statements, developed by Mateusz Marciniak. The results showed that the majority of the respondents (ca. 70%) never engaged in online fundraising campaigns, did not engage in political disputes online (more than 75%) and did not seek social support on the internet.